A Framework of Integrated Decision Support System for Students' Project Evaluation - Fadhilah, Ahmad; Ahmad Nazari, Mohd Rose; Elissa Nadia, Madi; Suhailan, Safei (2012)
At certain Institute of Higher Learning, the evaluation of students’ projects is done not only by a supervisor but also by a group of panels. The evaluation takes into consideration a number of criteria, a few of which are normally fuzzy in nature. The fuzziness of certain criteria makes the evaluation process complicated. The main evaluation criteria that are considered include project proposal document, final report document, prototype system, and oral presentation. All students’ projects need to be carefully evaluated based on these criteria to ensure that the students’ projects are rated fairly and be given standardized marks. A group decision support system is required to achieve the objective of fair and accurate evaluations. This research proposes a framework for students’ projects evaluation for Decision Support System based on the Weighted Model, Fuzzy Ranked Analytical Hierarchical Process and Fuzzy TOPSIS via a number of evaluation phases. At the end of the evaluation process, a list of sorted ranked marks is displayed to the users for further decision making activities to take place.